Large magnetic entropy change and magnetic properties in Gd60-xHoxFe20Al20 amorphous ribbons. (27th June 2018) - Wang, Fang; Lin, Jing-Ru; Ying, Hao; Feng, Tang-Fu; Sun, Ren-Bing; Li, Xie
Abstract: The magnetic entropy change (Δ S M ) and magnetic properties of amorphous ribbons Gd60-x Hox Fe20 Al20 (x = 10, 30 and 50) have been investigated. The partial substitution of Ho for Gd results in a monotonously decrease of phase transition temperature from 165 K to 65 K and an increase of maximal Δ S M from 5.44 J · Kg −1 K −1 to 8.01 J · Kg −1 K −1 under a field change of 0–5 T. Furthermore, a large value of relative cooling power (RCP) about 645 J.kg −1 is obtained in Gd10 Ho50 Fe20 Al20 amorphous ribbons. This material could be a very good candidate for magnetic refrigerant around the liquid nitrogen temperature region. It is also found that the amorphous ribbons with the same chemical composition fabricated at different spinning rate show the similar temperature dependence of magnetization behavior, the maximal Δ S M as well as saturated magnetization, however, increases with the spinning rate. It could be attributed to the different rate of solidification of the alloy.